The Error in Ethnomathematics Exploration on Silat Perisai in Kampar District - Wahyuni, Molli; Zulfah; Astuti; Zulhendri (LPPM Undiksha, 2022)
Silat Perisai is one of the cultural heritages of the Pucuk Adat, Kampar Regency, Riau Province, which has existed since before the independence of the Republic of Indonesia and since 2017 has been included in the Intangible Cultural Heritage. This study aims to evaluate the results of ethnomathematical exploration carried out by students of Mathematics Education at Pahlawan Tuanku Tambusai University in the Silat Perisai movement. This research is a descriptive study with a case study on ethnomathematical exploration in Silat Perisai. Researchers observed the exploration process carried out by students, and evaluated reports on exploration results. Student errors are viewed from two aspects, namely aspects of mathematical concept errors and aspects of ethnomathematical exploration procedures errors. Before carrying out the exploration, the student group first validated the research instruments used, such as observation sheets and interviews. The results showed that the overall level of error in disclosing ethnomathematical concepts of flat shapes reached 50%, which means that students' errors in expressing concepts are still relatively moderate. The procedural error rate in ethnomathematical exploration reaches 40%.